Langkah-Langkah dalam Pengembangan Kurikulum - Devy Habibi Muhammad; Noer Laili Rohmadhoni Novita Fitri; Nurul Lailatul Aulia; Nur Wahid (CV. Lentera Literasi Indonesia, 2026)
Curriculum development is a key element in improving the quality of education, directly impacting the learning process in schools. This article discusses the important steps in curriculum development, starting with needs analysis to determine what needs to be taught and learned by students, followed by the formulation of clear and measurable educational goals. Next, the process involves developing relevant teaching materials and selecting effective teaching methods, as well as proper implementation to ensure the curriculum is effectively carried out. Ongoing evaluation is also an essential part of ensuring the curriculum achieves the desired goals. Good curriculum development requires collaboration from various parties, such as educators, curriculum experts, and the community. This study aims to provide a deeper understanding of the steps involved in curriculum development in Indonesia, with the hope of helping to create a more effective curriculum that is relevant to the current needs of the education system.